2008
DOI: 10.1159/000108134
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of IgE-Binding to Art v 1, Art v 4 and Amb a 1 in Mugwort-Allergic Patients

Abstract: Background: Mugwort (Artemisia vulgaris) represents an important source of weed pollen allergens. The objectives of the present study were (i) to analyze the IgE binding profiles in a group of mugwort-allergic patients, (ii) to identify individual marker allergens crucial for the diagnosis of mugwort allergy and (iii) to identify potential crossreactive allergens present in ragweed (Ambrosia artemisiifolia) pollen extract. Methods: Sera from 100 pediatric mugwort-allergic patients were analyzed for their IgE b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 42 publications
5
29
0
2
Order By: Relevance
“…This is consistent with epidemiological studies that indicate that only a single allergenic source, probably that providing the highest profilin exposure, may be responsible for triggering IgE response to profilins (23). Moreover, IgE cross-reactivity to ragweed allergen Amb a 1 of sera derived from mugwort allergic patients living in the area with no ragweed exposure has been reported (46). In summary, our study provides evidence for the existence of a specific IgE response to well characterized profilins Art v 4 and Amb a 8 and demonstrates the differences in IgE binding between weed profilins and tree profilins, which are related to the structural differences of those proteins.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with epidemiological studies that indicate that only a single allergenic source, probably that providing the highest profilin exposure, may be responsible for triggering IgE response to profilins (23). Moreover, IgE cross-reactivity to ragweed allergen Amb a 1 of sera derived from mugwort allergic patients living in the area with no ragweed exposure has been reported (46). In summary, our study provides evidence for the existence of a specific IgE response to well characterized profilins Art v 4 and Amb a 8 and demonstrates the differences in IgE binding between weed profilins and tree profilins, which are related to the structural differences of those proteins.…”
Section: Discussionsupporting
confidence: 90%
“…The recombinant profilins were recognized by IgE from some allergic patients, which is consistent with previous reports (21,27,45,46). Several studies have demonstrated that IgE from patients sensitized to one profilin binds to profilins from all other sources (40,41).…”
Section: Discussionsupporting
confidence: 90%
“…However, no information about sensitization to whole mugwort pollen extract was given [8]. The prevalence of IgE reactivity to Art v 1 of 84% in mugwort-sensitized subjects from North Europe found in the present study is similar to the prevalence of 79% recently reported for mugwort-allergic subjects in Germany [22]. In the German study, 14% of the subjects were sensitized to Amb a 1; this percentage is also similar to the corresponding prevalence figures obtained for the European subjects in our study.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, nArt v 1 is considered a true major mugwort pollen allergen, accounting for IgE-sensitization in approximately 80% of mugwort-pollen-allergic patients [59,60]. Importantly, it is an effective marker of genuine sensitization to mugwort pollen, even when cross-reactivity to minor ragweed allergen Amb v 4 occurs [61].…”
Section: Markers Of Genuine Sensitization To Major Pollen Sourcesmentioning
confidence: 99%